PENGARUH KUALITAS PRODUK, KEWAJARAN HARGA DAN NILAI PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SKINCARE SKINTIFIC DI KOTA BATAM - jassica; Pitri Nainggolan, Nora (LPPM Universitas Putera Batam, 2024)
This research aims to examine the influence of product quality, price fairness and customer value on consumer purchasing decisions for Skintific Skincare in Batam City. This research uses an associative method with a quantitative research type. The research sample consisted of 100 respondents who were people who had purchased and used Skintific Skincare in the Sungai Pelunggut Village area, Sagulung District, Batam City. The data collection method used is primary data. Data processing uses the SPSS Version 26 program. Based on the data and analysis that has been carried out, this research shows that product quality positively and significantly influences consumer purchasing decisions for Skintific Skincare in Batam City. Apart from that, price fairness positively and significantly influences consumer purchasing decisions for Skintific Skincare in Batam City. The customer value variable positively and significantly influences consumer purchasing decisions for Skintific Skincare in Batam City. And simultaneously, product quality, price fairness and customer value positively and significantly influence consumer purchasing decisions for Skintific Skincare in Batam City.